Aplikasi Mobile Pengenalan Kebudayaan Indonesia Berbasis Android - Cahyadisaputro, Barma; Sutanto, Teguh; Karsam, Karsam (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2015)
Existing conditions, introduction of information media culture generally use the book, where in it contains names and images of culture and culture is not explicitly about the description of the culture, so that the user understands a little less on the diversity of Indonesian culture. As more and more Android-based smartphone users, it can be used to help introduce Indonesian culture by developing Android based applications. This application is designed to convey information such as name, picture, and description of the traditional house, traditional clothing, traditional dances, musical instruments and traditional weapons area. On the application displays cultural features, these features cultural displays one of five categories of culture, then features the logo of the 33 provinces, this display features 5 categories of culture from one province. Another feature is the search, the user can input the keywords of the culture in this feature. With the construction of the introduction of mobile applications based on android Indonesian culture, can help introduce and visualize the community, especially the students in the study of diverse cultures such as traditional houses, traditional clothing, traditional dances, musical instruments and traditional weapons area of 33 provinces in Indonesia. Where the 24 respondents have high enthusiasm for this application and 6 respondents had low enthusiasm.